Eye movement feedback fails to improve visual search performance - Peltier, Chad (Cogn Res Princ Implic, 2017)
Many real-world searches (e.g., radiology and baggage screening) have rare targets. When targets are rare, observers perform rapid, incomplete searches, leading to higher miss rates. To improve search for rare (10% prevalence) targets, we provided eye movement feedback (EMF) to observers during their searches. Although the nature of the EMF varied across experiments, each method informed observers about the regions of the display that had not yet been inspected. We hypothesized that feedback would help guide attention to unsearched areas and increase the proportion of the display searched before making a target-absent response, thereby increasing accuracy. An eye tracker was used to mark fixated areas by either removing a semiopaque gray overlay (Experiments 1 and 4) as portions of the display were fixated or by adding the overlay once the eye left a segment of the image (Experiments 2 and 4). Experiment 3 provided automated EMF, such that a new region was uncovered every 540 milliseconds. Across experiments, we varied whether people searched for “Waldo” in images from “Where’s Waldo?” search books or searched for a T among offset Ls. We found weak evidence that EMF improves accuracy in Experiment 1. However, in the remaining experiments, EMF had no effect (Experiment 4), or even reduced accuracy (Experiments 2 and 3). We conclude that the one positive result we found is likely a Type I error and that the EMF method that we used is unlikely to improve visual search performance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s41235-017-0083-2) contains supplementary material, which is available to authorized users.